Development of Re-Hits (Adolescent Reproductive Health): Android Application as A Strategy to Increase Adolescent Knowledge about Reproductive Health - Saprina, Putri; Nadira, Nindy Audia; Amos, John (POLTEKKES KEMENKES PADANG, 2024)
Adolescence is a transitional period from childhood to adulthood characterized by high vulnerability to sexually transmitted infections and various reproductive health issues. Currently, teenagers in Indonesia constitute 24% of the total population. An urgent issue identified is the high prevalence of unwanted pregnancies among teenagers aged 14-19, standing at 19.6%, with 20% of these cases resulting in abortions. Moreover, a significant number of teenagers have been exposed to sexual activities through online media. This occurrence is attributed to teenagers facing challenges in accessing reliable information about reproductive health and risky sexual behavior. Therefore, the authors innovated with a promotive media called REHITS (Reproductive Health In Teenagers). The main objective is to examine the influence of the REHITS application on improving teenagers' knowledge about reproductive health. This research employs a quantitative method. The application was designed using the development method developed by Luther (1994). It includes features such as educational videos, articles, podcasts, posters, FAQs, and a chatbot. Of the participants who used the REHITS application, 87% found the provided information helpful, found the application interface engaging, and encountered no errors during its use. Thus, there is an influence of the development of the REHITS application on increasing teenagers' knowledge about reproductive health management.